OmpR, a response regulator of the two-component signal transduction pathway, influences inv gene expression in Yersinia enterocolitica O9 - Brzóstkowska, Marta; Raczkowska, Adrianna; Brzostek, Katarzyna (Frontiers in Cellular and Infection Microbiology, 2012)
The environmental control of invasin (inv) expression in Yersinia enterocolitica is mediated by a regulatory network composed of negative and positive regulators of inv gene transcription. Previously, we demonstrated that OmpR, a response regulator of the two-component signal transduction pathway EnvZ/OmpR, negatively regulates inv gene expression in Y. enterocolitica O9 by direct interaction with the inv promoter region. This study was undertaken to clarify the role of OmpR in the inv regulatory circuit in which RovA protein has been shown to positively regulate inv transcription. Using ompR, rovA, and ompR rovA Y. enterocolitica mutant backgrounds we showed that the inhibitory effect of OmpR on inv transcription may be observed only when RovA is present/active in Y. enterocolitica cells. To extend our research on inv regulation we examined the effect of OmpR on rovA gene expression. Analysis of rovA-lacZ transcriptional fusion in Y. enterocolitica wild-type and ompR background indicated that OmpR does not influence rovA expression. Thus, our results indicate that OmpR influences inv expression directly via binding to the inv promoter, but not through modulation of rovA expression.